New biological tools for the study of plant systems in modern biotechnology - Bronnikova, L.I.; Zaitseva, I.O. (Problems of Environmental Biotechnology, 2023)
Genetic control is exerciesed at all stages of growth and development of the plant system. The plant metabolism is coordinated according to the integraction of direct and cross-talk between al vital systems, which are established and constantly evolve in the from of dynamic phenotypic effects. The acquisition of biological information improvement of methods and research.